2012
DOI: 10.3109/09638288.2012.711898
|View full text |Cite
|
Sign up to set email alerts
|

Combining strength training and botulinum neurotoxin intervention in children with cerebral palsy: the impact on muscle morphology and strength

Abstract: Cerebral Palsy• Botulinum toxin type-A (BoNT-A) and strength training are available interventions that, on their own have found success in managing spasticity and muscle weakness (both significant motor impairments), respectively in children with Cerebral Palsy (CP). • This study has demonstrated that the concurrent treatment of BoNT-A and strength training can achieve positive outcomes in terms of strength, spasticity and for the achievement of set functional goals. • The results of this study show that the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
130
2
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(138 citation statements)
references
References 32 publications
2
130
2
4
Order By: Relevance
“…The remaining five studies were all prospective designs, including two randomised cohort studies (Moreau et al, 2013;Stackhouse et al, 2007), two cohort follow-up studies (Lee et al, 2013;McNee et al, 2009), and one cross-comparison study (Williams et al, 2013). Of these five non-randomised controlled studies, three studies investigated predominantly home-based lower limb strength training (McNee et al, 2009;Stackhouse et al, 2007;Williams et al, 2013), one study evaluated the effects of isokinetic strength training in a tertiary setting (Moreau et al, 2013), and one study utilised an upper limb strengthening intervention administered within a tertiary institution (Lee et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The remaining five studies were all prospective designs, including two randomised cohort studies (Moreau et al, 2013;Stackhouse et al, 2007), two cohort follow-up studies (Lee et al, 2013;McNee et al, 2009), and one cross-comparison study (Williams et al, 2013). Of these five non-randomised controlled studies, three studies investigated predominantly home-based lower limb strength training (McNee et al, 2009;Stackhouse et al, 2007;Williams et al, 2013), one study evaluated the effects of isokinetic strength training in a tertiary setting (Moreau et al, 2013), and one study utilised an upper limb strengthening intervention administered within a tertiary institution (Lee et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…A detailed description of all intervention characteristics of the included studies is shown in Table 2 2013; Stackhouse et al, 2007;Williams et al, 2013), and one study implemented an upper limb strengthening programme (Lee et al, 2013). None of the included studies had a pure control group that received no intervention.…”
Section: Types Of Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, children with CP in South Africa often had to wait very long periods for medical appointments, and they lacked medical treatment in terms of evidence-based medicine, such as BoNT-A (Williams et al, 2013) and CITB (Vles et al, 2013). Our study showed that it was a challenge to access this kind of medication, mostly due to financial constraints.…”
Section: Contextual Factorsmentioning
confidence: 86%
“…As orally administered medication does not always reduce pain in children with CP, alternatives could be implemented with other types of medication, such as continuous intrathecal baclofen (CITB) therapy (Vles et al, 2013) or botulinum toxin type-A (BoNT-A; Williams et al, 2013). Examples of complementary methods that could be implemented are strength training to manage spasticity and muscle weakness (Williams et al, 2013), massage therapy (Nilsson, Johansson, Enskär, & Himmelmann, 2011), selective dorsal rhizotomy for reducing muscle spasticity, casting for improving and maintaining ankle range of motion, and neurodevelopmental treatment (NDT), also known as the Bobath concept. NDT includes facilitating handling techniques related to positioning and is commonly implemented for specific functional tasks aimed at treating children in actual life settings, i.e., where they live, play, and learn (Novak et al, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%